2012
DOI: 10.1111/j.1523-1739.2012.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Disease Risks Associated with Translocations

Abstract: Translocations of species are expected to be used increasingly to counter the undesirable effects of anthropogenic changes to ecosystems, including loss of species. Methods to assess the risk of disease associated with translocations have been compiled in a comprehensive manual of disease-risk analysis for movement of domestic animals. We used this manual to devise a qualitative method for assessing the probability of the occurrence of disease in wild animals associated with translocations. We adapted the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 35 publications
0
89
0
Order By: Relevance
“…While explicit risk assessment and risk management frameworks have been proposed and applied in wildlife translocation projects, effective application requires at least qualitative knowledge of pathogens, vectors, and susceptibilities operating in the given species (e.g., Lenihan et al, 1999; Sainsbury & Vaughan-Higgins, 2012). The limited use of multidisciplinary effective diagnostic tools and lack of robust etiological characterization for coral disease in general, and in A. cervicornis in particular (Rogers, 2010; Sutherland, Porter & Torres, 2004), impairs efficient health risk management.…”
Section: Introductionmentioning
confidence: 99%
“…While explicit risk assessment and risk management frameworks have been proposed and applied in wildlife translocation projects, effective application requires at least qualitative knowledge of pathogens, vectors, and susceptibilities operating in the given species (e.g., Lenihan et al, 1999; Sainsbury & Vaughan-Higgins, 2012). The limited use of multidisciplinary effective diagnostic tools and lack of robust etiological characterization for coral disease in general, and in A. cervicornis in particular (Rogers, 2010; Sutherland, Porter & Torres, 2004), impairs efficient health risk management.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial that we characterise how wildlife respond to research and conservation interventions such as capture and handling (de Villiers et al 1995;Narayan et al 2012) and translocation (Kahn et al 2007) to assess risk, minimise harm and increase the efficacy of these activities. For example, it has been suggested that the stress of translocation is associated with increased risk of infectious disease in translocated wildlife (Teixeira et al 2007;Dickens et al 2010;Sainsbury and Vaughan-Higgins 2012), including recrudescence of latent and normally innocuous pathogens as well as increased vulnerability to diseases at the release site to which the translocated animals may not have been previously exposed (Mihok et al 1992). However, parallel endocrine and infection investigations have rarely been conducted before, during and after wildlife translocations or, indeed, in instances of wild capture (moving of wild animals into captivity), to investigate the influence of stress and disease in translocation success and the health of translocated and resident populations.…”
Section: (3) Wildlife Management Interventionsmentioning
confidence: 99%
“…For example, wild boar (Sus scrofa) has reestablished in several parts of Britain through escapes from farms, but many of these populations contain domestic pig hybrids (Wilson, 2005). Other British species, such as roe deer, crane and red kite (Milvus milvus), consist of remnant native or natural recolonist populations that have been supplemented with individuals from mainland Europe to increase their viability (Evans et al, 1999;Yalden, 1999;Sainsbury and Vaughan-Higgins, 2012). The genetic status of other native species is being altered through hybridisation with domestic or feral counterparts, for example Eurasian wildcat with domestic cat (Felis catus) (Oliveira et al, 2008;O'Brien et al, 2009).…”
Section: The Genetic Identity Of Native Speciesmentioning
confidence: 98%